A bioinspired optimization strategy: to minimize the travel segment of the nozzle to accelerate the fused deposition modeling process - Sundarraj, Sridhar; K , Aditya; Ramamoorthi , Venkatraman; M., Venkatesan (Bulletin of the Polish Academy of Sciences Technical Sciences, 2023)
The fused deposition modeling process of digital printing uses a layer-by-layer approach to form a three-dimensional structure. Digital printing takes more time to fabricate a 3D model, and the speed varies depending on the type of 3D printer, material, geometric complexity, and process parameters. A shorter path for the extruder can speed up the printing process. However, the time taken for the extruder during printing (deposition) cannot be reduced, but the time taken for the extruder travel (idle move) can be reduced. In this study, the idle travel of the nozzle is optimized using a bioinspired technique called "ant colony optimization" (ACO) by reducing the travel transitions. The ACO algorithm determines the shortest path of the nozzle to reduce travel and generates the tool paths as G-codes. The proposed method’s G-code is implemented and compared with the G-code generated by the commercial slicer, Cura, in terms of build time. Experiments corroborate this finding: the G-code generated by the ACO algorithm accelerates the FDM process by reducing the travel movements of the nozzle, hence reducing the part build time (printing time) and increasing the strength of the printed object.